Radiological response and histological findings in nephroblastoma: Is the any correlation? - Pamela Josephine Middleton; Berhouz Banieghbal; Richard Denys Pitcher; Pawel Schubert (Wolters Kluwer Medknow Publications, 2020)
Introduction: The Sociétè Internationale d'Oncologie Pédiatrique advocates for neoadjuvant chemotherapy in the management of nephroblastoma. Postoperatively, histological findings are used to assign risk classification to resected tumours. The aim of this study is to compare the response demonstrated by pre-operative imaging to the amount of necrosis seen on histology postoperatively. Patients and Methods: About 33 patients with nephroblastoma over a 10 year period had adequate imaging and histology records for this study. Three methods were used to assess tumour change following neoadjuvant therapy and were compared with histological records. 1. An estimation of necrosis, 2. Surface areas of apparent necrosis within the tumour measured on static imaging, 3. The change in volume of the mass. Pearson coefficient was calculated to measure the correlation between histologically observed necrosis and radiological changes. Results were considered significant if P< 0.05. Results: There was no correlation between radiological changes on pre-operative imaging and the percentage of necrosis seen on histology. Change in tumour size on radiological studies showed a moderate correlation to percentage tumour necrosis on histology but was unable to predict tumour risk classification. Conclusions: In nephroblastoma, there is a moderate correlation between the decrease in size of a mass noted on imaging following chemotherapy and the degree of necrosis found postoperatively on histology. Change in tumour size cannot be used to predict histological risk classification. It is not possible to predict the histological risk classification of a nephroblastoma based on the changes demonstrated on non-contrasted magnetic resonance imaging or computed tomography preoperatively.